The effects of cholesterol on the viability and fertility of bull spermatozoa - Polmer Situmorang (Indonesian Center for Animal Research and Development (ICARD), 2002)
This study was conducted to evaluate the effect of cholesterol on the viability and fertility of chilled and deep-frozen bull spermatozoa. Semen was collected by means of artificial vagina, diluted in Tris-Citrat diluent and cooled to 50C for 60 minutes. Following an equiliberation for 4 hours, semen was frozen at 5 cm above surface of liquid nitrogen for 10 minutes. The experiment was 2 x 3 factorial designed with two level of egg yolk (10 and 20% v/v) and 3 level of cholesterol (0; 0.5 and 1.0 mg/ml). The viability of spermatozoa was evaluated after the temperature reduced to 50C, stored at 50C for 1, 3 and 7 days and after thawing. For fertility test, cows were artificially inseminated (AI) using chilled and frozen semen on the onset or 6 hours of oestrus. Rectal palpation was conducted 3 months after AI to determine the pregnancy. The percentages motile of chilled semen was higher in 0.5 mg/ml than those of 0.0 or 1.0 mg/ml cholesterol but this difference was not significant. After thawing, the effects of cholesterol on the percentage motile was significant (P<0.05). The mean percentage motile was 47.5; 51,5 and 56.0 for 0.0; 0.5 and 1.0 mg/ml cholesterol respectively. The percentage of live sperm and intact apical ridge was higher in cholesterol however this effects was not significant. The effects level of egg yolk and its interaction with cholesterol on the viability was not significant. The percentage of pregnant was higher in 1.0 mg/ml and the mean percentage of pregnant was 45.8; 48.2 and 55.7 for 0.0; 0.5 and 1.0 mg/ml cholesterol respectively. Percentage of pregnant was higher for chilled semen than those of frozen semen (54.3 vs 45.5). In conclusion the addition of 1 mg/ml cholesterol increase the percentage of motile after thawing and pregnancy of cows inseminated with chilled and frozen semen. Key words: Semen, viability, cholesterol, pregnan